Frontoethmoidal giant cell reparative granuloma. - Felsberg, G J; Tien, R D; McLendon, R E (American Journal of Neuroradiology, 1995)
We present a case of a giant cell reparative granuloma of the frontoethmoidal region that had a large intracranial extraaxial component and was studied with MR. Although rare, giant cell reparative granuloma can be suggested in the correct clinical setting and when MR features suggest a fibrous lesion.